2010
DOI: 10.1093/rheumatology/keq175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-oxidant treatments in an in vitro model of alkaptonuric ochronosis

Abstract: Our model allows the opening of new anti-oxidant therapeutic strategies to treat alkaptonuric ochronosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 42 publications
5
52
1
Order By: Relevance
“…Although the molecular mechanisms underlying alkaptonuria and especially ochronotic arthropathy have not been fully elucidated, we provided evidences suggesting an important role for oxidative stress induced by HGA auto-oxidation into BQA (Braconi et al 2010a;Braconi et al 2010b;Tinti et al 2010), corroborating very early in vitro studies demonstrating the production of ROS such as H 2 O 2 e O 2¯˙d uring this reaction (Martin and Batkoff 1987).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Although the molecular mechanisms underlying alkaptonuria and especially ochronotic arthropathy have not been fully elucidated, we provided evidences suggesting an important role for oxidative stress induced by HGA auto-oxidation into BQA (Braconi et al 2010a;Braconi et al 2010b;Tinti et al 2010), corroborating very early in vitro studies demonstrating the production of ROS such as H 2 O 2 e O 2¯˙d uring this reaction (Martin and Batkoff 1987).…”
Section: Resultssupporting
confidence: 78%
“…The HGA concentration we tested in our model, 0.33 mM (Braconi et al 2010a;Braconi et al 2010b;Tinti et al 2010), is in the range of circulating HGA in AKU patients' serum (between 50 and 400 μM) (Angeles et al 1989). …”
Section: Resultsmentioning
confidence: 99%
“…From our observations, HGA significantly preserved lipoproteins and liposomes from oxidative damage induced by Cu 2+ ions, and showed remarkable protective effect on the reduction of the levels of total PUFA/cholesterol, inhibiting the increase of their oxidative products. Several evidences suggest that the accumulation of HGA and benzoquinone acetate, a by-product of HGA oxidation, is implicated in inflammation and tissue degeneration observed in alkaptonuria (Braconi et al, 2010;Phornphutkul et al, 2002). Despite the controversial literature results, HGA, in our experimental conditions, showed a significant in vitro protective effect in different systems of oxidative stress, inhibiting the degradation of biological molecules (cholesterol and unsaturated fatty acids).…”
Section: Resultsmentioning
confidence: 60%
“…doi:10.1016/j.foodchem.2011.05.072 effects and it appears to occur through an oxidative mechanism based on the ability of this compound to undergo autoxidation, leading to quinone formation with the production of reactive oxygen species (Hiraku, Yamasaki, & Kawanishi, 1998;Urios et al, 2003). The accumulation of HGA in connective tissues, the formation of its oxidised/polymerised products and oxygen radical generation have been implicated in aetiology of ochronosis, inflammation and tissue degeneration observed in patients with alkaptonuria, a rare genetic disease associated with deficient homogentisate 1,2-dioxygenase activity in the liver (Braconi et al, 2010;Phornphutkul et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work (Braconi et al, 2010,b; Tinti et al, 2010; Tinti et al, 2011a,2011b; Braconi et al, 2012; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013) suggested that morphological changes of chondrocytes in AKU cartilage may be attributed to apoptosis, but until now no in depth study exists to elucidate if chondroptosis may occur in AKU. Moreover, ultra‐structural observations were complemented with biochemical and proteomic characterization of chondrocytes isolated from the ochronotic cartilage of AKU patients, indicating that AKU chondrocytes are characterized by HGA‐induced apoptosis, protein aggregation, nitric oxide release, and oxidative stress (Tinti et al, 2011a; Laschi et al, 2012; Millucci et al, 2012; Braconi et al, 2013; Spreafico et al, 2013).…”
mentioning
confidence: 99%